Effects of Working Memory, Strategy Use, and Single-Step Mental Addition on Multi-Step Mental Addition in Chinese Elementary Students - Ding, Yi; Liu, Ru-De; Liu, Hongyun; Wang, Jia; Zhen, Rui; Jiang, Rong-Huan (Frontiers in Psychology, 2019)
The aim of this paper was to examine the roles of working memory, single-step mental addition skills, and strategy use in multi-step mental addition in two independent samples of Chinese elementary students. In Study 1, we manipulated strategy types through the dimension of schema automaticity (whether intermediate sums were 10s) and the dimension of working memory load (WML, two steps versus four steps). A hierarchical linear model (HLM) analysis was conducted at case level, strategy level, and individual level. In Study 2, we manipulated task characteristics through schema automaticity (one-time versus two-time regrouping) and the WML (partial versus complete decomposition). A three-level HLM analysis was applied. The general findings of Study 1 and Study 2 suggested that response time on single-step mental addition positively predicted response time on multi-step mental addition (faster response time on single-step mental addition corresponded to faster response time on multi-step mental addition). The use of strategies (from easier to more difficult strategies) negatively predicted response time on multi-step mental addition. Easier strategy was associated with shorter response time on multi-step mental addition. Phonological loop skills negatively predicted response time on multi-step mental addition. Better phonological loop was associated with shorter response time on multi-step mental addition.